Health shocks and overindebtedness: A panel data analysis from rural Viet Nam - Panharoth Chhay; Dil Bahadur Rahut (Asian Development Bank Institute (ADBI), 2022)
Rural households in developing countries have limited capacity to cope with and manage shocks, thereby resulting in chronic poverty, indebtedness, and a decline in overall well-being. Therefore, this study analyzes the effects of health shocks on overindebtedness in rural Viet Nam using four rounds of a balanced panel data set of about 1,750 households observed over a decade (2007, 2010, 2013, 2016). Employing the household-level fixed-effect model, this study finds that health shocks reduce household income and increase health expenditure among rural Vietnamese households. It also finds that households cope with health shocks mainly by borrowing from more sources. Households experiencing health shocks are 2.2 to 3.1 percentage points more likely to be overindebted, which occurs primarily among households without health insurance, suggesting that social health insurance can reduce households' vulnerability to the consequences of health shocks. These findings strongly support efforts to expand access to social health insurance in rural Viet Nam.
Keywords: E21; E24; I13; I15; 330; health shocks; overindebtedness; social health insurance; household-level fixed effects; rural Viet Nam